לפשט ( 8 + 9)?

לפשט ( 8 + 9)?
Anonim

תשובה:

#sqrt (sqrt8 + sqrt9) = 1 + sqrt2 #

הסבר:

תן #sqrt (sqrt8 + sqrt9) = sqrta + sqrtb #

מתיישר # sqrt8 + sqrt9 = a + b + 2sqrt (ab) # וכמו # sqrt9 = 3 #, יש לנו # a + b + 2sqrt (ab) = 3 + sqrt8 = 3 + 2sqrt2 #

לפיכך # a + b = 3 # ו # ab = 2 #

כלומר # a = 3-b # ולכן # (3-b) b = 2 # או # 3b-b ^ 2 = 2 #

או # b ^ 2-3b + 2 = 0 # כלומר # (b-2) (b-1) = 0 #

לכן # b = 1 # או #2#.

ואז # a = 2 #או # a = 1 #

שימו לב שהם מובילים לפתרון זהה

לפיכך #sqrt (sqrt8 + sqrt9) = sqrt1 + sqrt2 = 1 + sqrt2 #